Lexicogrammatical Features in Japanese English: A Study of Five Speakers - Yamaguchi, Toshiko (Research in Language, 2018)
Japanese English (JE) refers to the English spoken by Japanese citizens. This paper characterizes JE by examining its lexicogrammatical features produced by five speakers participating in experimental recordings. Drawing on the initiatives taken by Cogo and Dewey’s seminal work (2012), this study presents nine lexicogrammatical features which are taken to be typical of JE. It is shown that one decisive factor in creating a new variant is the formation of an alternative form to its native counterpart and this mechanism is sourced from the speaker’s multiple knowledge about two languages.